PENGGUNAAN MODEL PEMBELAJARAN RME UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA (STUDI KELAS IV SD 92 PALLAWARUKKA KABUPATEN WAJO) - Firdaus, Firdaus; Satriani, DH, Satriani, DH; Andi Indrayani, Andi Rezky (Universtas Negeri Makassar, 2024)
This study is a classroom action research that aims to find out how to use the RME learning model to improve the Mathematics learning outcomes of grade IV students of SD Negeri 92 Pallawarukka Wajo Regency. Data collection techniques use observation and tests. Data analysis techniques in this study are reducing data, describing data, and drawing conclusions. The results showed that the percentage of teacher activity in cycle I meeting 1 was 55.55% (Less) and meeting 2 reached 77.77% (Good), while the percentage in cycle II meeting 1 was 85.18% (Good) and meeting 2 reached 92.59% (Good). The percentage of student activity in Cycle I Meeting 1 was 44.44% (Less) and Meeting 2 reached 55.55% (Less), while the percentage in Cycle II meeting 1 was 66.66% (Enough), while in Meeting 2 reached 85.18% (Good). In the acquisition of student learning outcomes in the first cycle there were 11 out of 15 completed students with an average score of 79 with a percentage of learning completeness reaching 73.33% (Enough), while in the second cycle, there were 13 out of 15 students achieving complete scores with an average score of 88 with a percentage of learning completeness reaching 86.66% (Good). It can be concluded that the RME learning model can improve students' Mathematics learning outcomes.